Measuring Inflation Expectations in Interwar Britain - Jason Lennard; Finn Meinecke; Solomos Solomou (Center for Economic Studies and ifo Institute (CESifo), 2021)
What caused the recovery from the British Great Depression? A leading explanation - the “expectations channel” - suggests that a shift in expected inflation lowered real interest rates and stimulated consumption and investment. However, few studies have measured, or tested the economic consequences of, inflation expectations. In this paper, we collect high-frequency information from primary and secondary sources to measure expected inflation in the United Kingdom between the wars. A VAR model suggests that inflation expectations were an important source of the early stages of economic recovery in interwar Britain.
Keywords: E30; E60; N14; 330; policy regime change; economic history; Great Depression